Analisis Kinerja Kincir Air Tipe Undershot Bahan Aluminium Dengan Jumlah 10 Sudu dan Sudut 20⁰ - Muhammad Idris; Indra Hermawan; Bongot Halomoan Simamora (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
To produce ideal electrical energy, a waterwheel with decent efficiency is needed. The appearance of a waterwheel can be affected by several limitations, including the size of the edges, the speed at which the water flows, and the number of edges entered. In addition, it is also essential to align the water wheel with the river frame so that the wheel is divided into three types, namely overshot, breastshot, and undershot. The undershot water wheel works on the flow of water, which causes movement around the bottom of the wheel. Although the design is essential and affordable, this type is suitable for use in shallow waters in flat areas and is not difficult to move. The procedure in this study was carried out by analyzing the performance of a micro-hydro power plant consisting of discharge, torque, and efficiency. The maximum electric power produced by the undershot type water wheel with 10 blades at a blade angle of 20⁰ with aluminum material is 5.7 Watt with a water discharge of 0.00546 m3/s, and the minor electric power is 4.2 Watt; this power is obtained at the discharge water of 0.00429 m3/s. This type of undershoot waterwheel can be implemented in areas that have flowing rivers or waterfalls so that it can become an alternative power plant. This study concludes that the maximum electric power produced by an undershot type water wheel with 10 blades at a blade angle of 20⁰ with aluminum material is 5.7 Watt with a water discharge of 0.00546 m3/s, and the smallest electric power is 4.2 Watt; this was obtained at a water debit of 0.00429 m3/s.